Project Amihan: Online Air Monitoring System for Selected Areas along McArthur Highway, Valenzuela City - Espinoza, Dave L.; Iban, Mark Ferdinand A.; Torres, Jam Christian A.; Villarama, Prince Carl R.; Velasco, Londren U.; Comandao, Abegail S.; Santos, Walfredo G.; Montaos, Cris Mabel C. (International Journal of Computing Sciences Research; Vol 2 No 1 (2018): Vol 2, No 1, 2018)
Purpose – Air pollution, through the years, is a major problem in the Philippines. Different illnesses came about as its consequence. To mitigate air pollution particularly in Valenzuela, the Department of Environment and Natural Resources with the help of Valenzuela City Government’s City Environment and Natural Resources Office installed an air monitoring system. Inspired by such technological innovation, the researchers aimed to design and develop “Project Amihan: Online Air Monitoring System for Selected Areas along McArthur Highway, Valenzuela City.” The study is significant to Valenzuela residents along McArthur Highway, to the community, educational institutions, the government, and future researchers. Method – For data gathering, survey and interview was used. The researchers’ method was Agile Prototyping Model and they used Arduino Uno microcontroller, wi fi module, gas sensors, and jumper wires for the hardware; HTML, PHP, JavaScript, jQuery, Ajax to develop the website and embed the system, as well as a webhost to disseminate information. The system was tested in four (4) selected areas along McArthur Highway of Valenzuela namely: Balintawak Beer Brewery (BBB), Fatima, Karuhatan, and Malinta. Twenty (20) Valenzuela residents and five (5) IT Experts served as respondents who evaluated the system. Five-point Likert Scale using the ISO 9126 as the standard reference was used to evaluate it. Results – The system was evaluated 4.17 or Very Acceptable by the end-users, 4.49 or Very Acceptable by the IT Experts and garnered an overall mean of 4.33 which is equivalent to Very Acceptable. The information derived from the air monitoring system was disseminated through a website and email notification to raise awareness by providing insights of what bad air may cause the residents. Conclusion – In conclusion, the system most notably detected Carbon Dioxide (CO2) gas in the air. It can monitor the Carbon Dioxide gas in the air as its innovation. Pollutants in the four selected locations varied at different time schedules. Such areas are not always polluted, but it happens mostly during rush hours. Recommendations - Users must sign up in the system to receive a notification if ever the air quality reaches the dangerous level; the city government – as the beneficiary of the said system – shouldprovide a stable internet connection for the system to have real-time monitoring of the air quality along McArthur Highway. Research Implications – Future developers must integrate more sensors to improve the accuracy of the current system and they may opt to integrate a renewable power source such as solar panel for the system so it can run even without the city’s electric power supply.